Novel Halotolerant Bacteria from Saline Environments: Isolation and Biomolecule Production - Simona Neagu; Mihaela Marilena Stancu (BioTech)
Microorganisms from saline environments have garnered significant interest due to their unique adaptations, which enable them to thrive under high-salt conditions and synthesize valuable biomolecules. This study investigates the biosynthesis of biomolecules, such as extracellular hydrolytic enzymes, biosurfactants, and carotenoid pigments, by four newly halotolerant bacterial strains isolated from saline environments in the Băicoi (soil, water) and Curmătura (mud) area (Prahova County, Romania). Isolation was performed on two selective culture media with different NaCl concentrations (1.7 M, 3.4 M). Based on their phenotypic and molecular characteristics, the four halotolerant bacteria were identified as Halomonas elongata SB8, Bacillus altitudinis CN6, Planococcus rifietoensis CN8, and Halomonas stenophila IB5. The two bacterial strains from the Halomonas genus exhibited growth in MH medium containing elevated NaCl concentrations (0–5 M), in contrast to the other two strains from Bacillus (0–2 M) and Planococcus (0–3 M). The growth of these bacteria under different salinity conditions, hydrocarbon tolerance, and biomolecule production were assessed through biochemical assays, spectrophotometry, and high-performance thin-layer chromatography. The antimicrobial properties of biosurfactants and carotenoids produced by H. elongata SB8, B. altitudinis CN6, P. rifietoensis CN8, and H. stenophila IB5 were evaluated against four reference pathogenic microorganisms from the genera Escherichia, Pseudomonas, Staphylococcus, and Candida. H. elongata SB8 showed the highest hydrocarbon tolerance. B. altitudinis CN6 exhibited multiple hydrolase activities and, along with H. elongata SB8, demonstrated biosurfactant production. P. rifietoensis CN8 produced the highest carotenoid concentration with antifungal and antimicrobial activity. Exploring these organisms opens new pathways for bioremediation, industrial bioprocessing, and sustainable biomolecule production.